2022
DOI: 10.1177/13634615221089384
|View full text |Cite
|
Sign up to set email alerts
|

Training in cultural psychiatry: Translating research into improvements in mental health care for migrants

Abstract: This special issue of Transcultural Psychiatry on training in cultural psychiatry discusses translating research into improvements in mental health care for refugees and migrants. This topic is timely because, in addition to a global increase in migration, the number of forcibly displaced people is growing rapidly due to war and conflicts. We know that migrants, particularly refugees, are at increased risk of psychiatric disorders, including psychotic disorders and post—traumatic stress. Despite this, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Lack of adequate support from the health care system and labor market may contribute to this observation. Moreover, somatic disorders might be underdiagnosed due to inadequate treatment of CMDs among the refugee young adults, which may further marginalize this vulnerable group ( 36 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of adequate support from the health care system and labor market may contribute to this observation. Moreover, somatic disorders might be underdiagnosed due to inadequate treatment of CMDs among the refugee young adults, which may further marginalize this vulnerable group ( 36 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CMDs among refugees may not be detected to the same extent as in their Swedish counterparts due to educational differences and a lack of consideration of cultural diversity competences in the assessment by health care professionals and other barriers such as stigmatization. Perceived CMDs symptoms differ by cultural background and could be underdiagnosed given a lack of culturally sensitive instruments ( 43 , 44 ). This may lead to lower psychiatric utilization and inadequate screening among refugee youths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of redefining therapeutic boundaries and the necessary implications this could have for the therapeutic care of refugees and asylum seekers is established in the literature (Bäärnhielm & Schouler‐Ocak, 2022; Karageorge et al, 2017; Kroll, 2001; Martinez, 2000; Savin & Martinez, 2006; Sandhu et al, 2013; Shors & Kroll, 2022). Traditional therapeutic boundaries have been highlighted as not being appropriate nor optimal in supporting refugees and asylum seekers and may disrupt rapport‐building.…”
Section: Introductionmentioning
confidence: 99%
“…A body of literature highlights that the mental health needs of refugees and asylum seekers have been best addressed through interdisciplinary and psychosocial work, practical interventions and advocacy; all of which lies within the remit of therapeutic boundary considerations (Karageorge et al, 2017). Reconsiderations and re‐conceptualizations of psychiatric and psychological boundaries with refugees have included modifying interactions with clients; offering interventions to clients based on their own cultural traditions; appropriate self‐disclosure as opposed to therapist anonymity; considering advocacy‐based, dual‐agency work as opposed to remaining neutral and transcending above therapeutic needs to address practical needs; and accepting small gifts and accepting clients' invitations to external events (Bäärnhielm & Schouler‐Ocak, 2022; Karageorge et al, 2017; Kirmayer, 2012; Savin & Martinez, 2006; Shors & Kroll, 2022). Extensive research has shown that refugee and asylum seeker clients identify practical assistance (e.g.…”
Section: Introductionmentioning
confidence: 99%